2021
DOI: 10.1016/s2213-2600(21)00286-1
|View full text |Cite
|
Sign up to set email alerts
|

The long-term sequelae of COVID-19: an international consensus on research priorities for patients with pre-existing and new-onset airways disease

Abstract: Persistent ill health after acute COVID-19—referred to as long COVID, the post-acute COVID-19 syndrome, or the post-COVID-19 condition—has emerged as a major concern. We undertook an international consensus exercise to identify research priorities with the aim of understanding the long-term effects of acute COVID-19, with a focus on people with pre-existing airways disease and the occurrence of new-onset airways disease and associated symptoms. 202 international experts were invited to submit a minimum of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 35 publications
3
90
0
3
Order By: Relevance
“…Very importantly, factors associated with those present in the acute period of the disease are not well known. As pointed out in a recent position manuscript, the recognition of factors associated with the acute period is a research priority for understanding the long-term sequalae of COVID-19 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Very importantly, factors associated with those present in the acute period of the disease are not well known. As pointed out in a recent position manuscript, the recognition of factors associated with the acute period is a research priority for understanding the long-term sequalae of COVID-19 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Вступ. Захворювання COVID-19 здатне завдати шкоди організму різними способами [3,7,9,11,13]. Його прояви змінюються від симптомів застуди до пневмонії та впливають на багато функцій і Developed laboratory work to study the structure and principle of operation of the pulse oximeter showed the possibility of diagnosing problems with the respiratory and cardiovascular systems in the early stages of their manifestation.…”
Section: компетентнісний підхід у вищій медичній освітіunclassified
“…Another limitation on the research on TMs against COVID-19 is the limited access to appropriate animal models, for example, transgenic hACE2 mice model (Bao et al, 2020) and cytokine storm syndrome mouse model induced by SARS-CoV-2 Spike protein (Gu et al, 2021). On the other hand, long COVID, the post-acute COVID-19 syndrome, has emerged as a major concern, which deserves further studies by using TMs (Adeloye et al, 2021). Overall, this research topic has been one of the first responses of the scientific communities globally to assess the potential of TM and here specifically TMs in addressing this major global health challenge.…”
Section: Perspectivesmentioning
confidence: 99%